Frozen Heat - Heller, Johnny ([New York] : Hyperion Audio, 2012)
When she discovers a connection between the homicide she is investigating and the unsolved murder of her mother, NYPD Homicide Detective Nikki Heat must expose her family's painful truths to stop a killer and solve the mystery that has tormented her for years.
Unabridged.
Fictitiously attributed to Richard Castle, a character on the ABC television show Castle.
Compact discs.
Read by Johnny Heller.
Keywords: Policewomen -- Fiction -- New York (State); Murder -- Fiction -- Investigation; Mystery fiction; Audiobooks